2019
DOI: 10.1111/ics.12541
|View full text |Cite
|
Sign up to set email alerts
|

Microrheological study of ternary surfactant‐biosurfactant mixtures

Abstract: Objective The main objective of this paper is to understand the rheological impact of rhamnolipids biosurfactant (mono/dirhamnolipids mixture, CCB) on a common personal care mixed surfactants system: anionic sodium laureth sulfate (SLES) and zwitterionic cocamidopropyl betaine (CAPB). The ternary biosurfactant/surfactants mixtures were evaluated at three different formulation conditions. The experimental results can provide a formulation guideline when applying rhamnolipids in cosmetics and personal care produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Although the SLES–CapB surfactant system is extensively used for its rheological properties, there are not a lot of studies that characterize its rheology and microstructure [18–21]. Mitrinova et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although the SLES–CapB surfactant system is extensively used for its rheological properties, there are not a lot of studies that characterize its rheology and microstructure [18–21]. Mitrinova et al .…”
Section: Introductionmentioning
confidence: 99%
“…Drakontis and Amin provide an overview different biosurfactant applications and various performance properties [6]. Studies have been conducted on the optimization of surface activity and rheological properties of various biosurfactants [6][7][8][9][10]. Biobased surfactants, on the other hand, are manufactured from biobased sources such as starches or sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Drakontis highlights various aspects of biosurfactant applications and properties critical to performance [6]. There have been studies on biosurfactant surface tension and rheology which have shown optimization of these properties, which can be achieved through variation of formulation variables; however, similar optimization studies to the best of our knowledge, have been very limited for biobased surfactants [6–10]. Biobased surfactants are derived from natural, biobased sources such as sugar and starches.…”
Section: Introductionmentioning
confidence: 99%